2022
DOI: 10.1186/s13031-022-00459-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting antenatal care utilization: a systematic review of 37 fragile and conflict-affected situations

Abstract: Background It is estimated that over 930 million people live in fragile and conflict-affected situations (FCAS) worldwide. These regions, characterized by violence, civil unrest, and war, are often governed by corrupt administrations who are unwilling to provide their citizens with basic human rights. Individuals living in FCAS face health inequities; however, women are disproportionally affected and face additional barriers to accessing sexual and reproductive services, including antenatal car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 138 publications
1
5
0
Order By: Relevance
“…Similar findings were observed in studies conducted in Iran and Malawi, indicating that maternity hospitals were advantageous for availability of specialist doctors, facilities for normal delivery, caesarean section, and good management, despite the crowdedness and lack of sufficient resources, which led to women seeking care there [ 35 37 ]. These factors not only drew women to facilities with one-stop services, but also helped them decide to return to there for pregnancy care [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were observed in studies conducted in Iran and Malawi, indicating that maternity hospitals were advantageous for availability of specialist doctors, facilities for normal delivery, caesarean section, and good management, despite the crowdedness and lack of sufficient resources, which led to women seeking care there [ 35 37 ]. These factors not only drew women to facilities with one-stop services, but also helped them decide to return to there for pregnancy care [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature identifies that infrastructure or lack of resources was a factor reported to impact access to ANC. Studies found that women who perceived operational and infrastructure problems in their community were deterred from accessing ANC and faced poorer health outcomes as a result [ 23 , 24 ]. A study in Pakistan in 2011 highlighted that women who gave birth in relief camps during the flood had no skilled birth attendants present, used unhygienic birth stations, and had poor postnatal services which increased the risk of mortality [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For ANC, there was no statistically significant positive upward trend as was expected for ANC1 rates, ANC5+ rates, rates of women seen in the first trimester of pregnancy, and rates of malaria cases in pregnancy seen in the health facility during ANC. As with health facility delivery, the conflict may explain this finding, especially as there is strong evidence that conflict affects ANC utilization in fragile and conflict-affected settings [ 27 ]. With employment opportunities limited in such settings, pregnant women may be challenged to secure the funds needed to pay for the service and transportation fees associated with ANC.…”
Section: Discussionmentioning
confidence: 99%